Human trafficking: the stakeholders' perspective - Mishra, Veerendra (SAGE Publications, 2013)
Introduction: Perspective, Cause and Effect of Human Trafficking / Veerendra Mishra. -- Part I: Gender prejudice: Commercial sexual exploitation. Civil Society Initiative of a Decade Against Human Trafficking: An Insider's Attempt at Looking Back / Pravin Patkar ; Bride Trafficking within India / M Shafiqur Rahman Khan ; Bar Dancer of Mumbai and Trafficked Migrant: Issues of Invisibility and Subaltern Existence / Flavia Agnes ; Globalisation, Sexuality and Human Trafficking / Preetha Prabhakaran ; Immoral Women or Victims? Prostitution in India / Trupti Jhaveri Panchal. -- Part II: Child trafficking: Less ado about silent exploitation. Trafficking of Children: Causes and Possible Solutions / Kailash Satyarthi ; Child Trafficking: The Alarm That Fails to Ring a Bell! / Bharti Ali ; Missing or Sold? Child Trafficking in India / CRY organization ; Breaking the Shackles of Bondage is Possible / Rakesh Senger ; Child Trafficking for Intercountry Adoption: Fight for Justice / Anjali Pawar ; A New Crisis: Experiences of Dealing with Emerging Trends in Child Trafficking in Delhi / Anant Kumar Asthana. -- Part III: Perspectives on trafficking from outside India. The Perverse Effects of the Hague Adoption Convention / Roelie Post ; Sexual Trafficking: Modern Slavery in the UK / Gary Craig ; Trafficking of Women in the Land of Sleeping Crocodile / Priyanka Mishra ; Dimensions of Trafficking in Women and Children in Bangladesh / Salma Ali ; The Final Act / Philip Holmes ; Challenges Faced by Trafficked Survivors in Bangladesh / Salima Sarwar and Uzzal Kumar Karmaker. -- Part IV: Law against human trafficking: From practitioners' lens. Human Trafficking: The Angle of Victimology / Justice Roshan Dalvi ; Immoral Traffic (Prevention) Act, 1956: A Concise Review / Swati A Chauhan ; On Operations and Rescue: Proper Police Procedure in Brothel Rescue Operations under ITPA / Advait Praturi, Michelle Mendonca and Emily Smith. -- Part V: Experiences of state responses. Combating Human Trafficking: Gaps in Law Enforcement / Veerendra Mishra ; Prevention of Human Trafficking: Dimensions and Strategies / P M Nair ; A Meaningful Research on Human Trafficking Translated into Action / Umapathi Sattaru ; Plights of Trafficked Laborers in the Circus Industry / Shrikar Pardeshi ; The Role of the Magistrate toward Trafficking Survivors / Levinson J Martins. -- Part VI: Cace studies and models - A way forward. Economic Rehabilitation: A Human Approach To Combat Human Trafficking / Arunendra Kumar Pandey ; Human Trafficking Scenario in Northeast India / Hasina Kharbhih ; Sex Trafficking, Health Care, and the Health System in Mumbai and Kolkata / Timothy P Williams, Elaine Alpert, Roy Ahn, Elizabeth Cafferty, Anita McGahan, Wendy Macias Konstantopoulos, Judith Castor Palmer, Nadya Wolferstan, Genevieve Purcell, and Thomas F Burke Women Trafficking in India: A Case Study of Women Sex Workers of Uttar Pradesh Awadhesh Kumar Singh and S P Pandey